Layer-by-layer construction of zwitterionic/biguanide polymers on silicone rubber as an antifouling and bactericidal coating. Issue 39 (13th September 2022) - Peng, Wan; Fan, Birong; Li, Youxin; Dong, Yaning; Qian, Weijian; Ji, Xiaoxue; Gan, Donglin; Liu, Pingsheng; Shen, Jian
Abstract : Layer-by-layer construction of antifouling/bactericidal coatings on silicone rubber. Abstract : Biofilm formation on biomedical devices is a major cause of device-associated infection. Traditional antibiotic treatment for biofilm-associated infection increases the risk of multidrug resistance. Thus, there is an urgent need to develop antibiotic-free strategies to prevent biofilm formation on biomedical devices. Herein, we report a layer-by-layer strategy to construct an antifouling and bactericidal dual-functional coating for silicone rubber (SR)-based substrates. Five zwitterionic active ester copolymers, p(SBMA- co -NHSMA), with varied zwitterionic pSBMA components that ranged from 50 to 90% (molar ratio) were precisely prepared. Based on –NH2 /NHS chemistry, a zwitterionic pSBMA antifouling coating was successfully constructed on an –NH2 -activated SR surface, while a biguanide polymer (PHMB) bactericidal coating was consequently tethered. The relationship between the composition of the polymeric coating and the overall antibacterial property (antifouling and bactericidal) that was endowed to the SR surface was established. The in vitro and in vivo results consistently showed that the optimal p(SBMA- co -NHSMA) copolymer (SBMA/NHSMA with molar percentage of 70/30) synergistically utilized antifouling and bactericidal abilities to endow a highly efficient overall antibacterial property (near 100% antibacterial ratios) to SR70-PHMB substrates without compromising cellular viability. This strategy may be applied to the many SR-based biomedical implants and devices where an antibacterial surface is required.